Implementación e implantación de la aplicación oficial institucional para dispositivos móviles en la unidad educativa "Bernardo Valdivieso" - Bustamante Pacheco, Paola Elizabeth (2014)
The folowing End of Carrer Project (ECP) describes the implementation and implant of the Institutional official application for Mobile Devices in the Educational Unit "Bernardo Valdivieso", allowing to make better the learning strategies using new information and communication technologies; that is why it has been considered deploying an application that provides services such as: Information of the institution more relevant, news, location of the institution on a map, player of hymns, direct access to Social Networks and Web Site, load-time teachers, schedule of classes and five months notes of the students. For the fulfilment of its established objectives of ECP, techniques are used for collecting information collecting techniques, such as the real or direct observation; the interview that was applied to the rector of this institution and to the Computing area while the surveys are employment to the students. For the processing, analysis and interpretation of the information management methods: scientific, inductive-deductive and biblioghaphy method. The application "Bernardine APP" consists of two parts, within the first part that is the Web Portal is used free tools such as the PHP language, the Apache web server and MySql as database manager; while in the mobile part used the framework phonegap the same which employs HTML5, CSS3 and javascript resulting hybrid applications, reducing the time and costs, in addition to providing increased security and stability in the information being handled. The system has been built following a RAD methodology for the development of the application, to be one of the most known and used today in addition to be a tool that allows the rapid and agile development through stages, covering the entire life cycle of a project.